2017
DOI: 10.1038/s41598-017-08022-w
|View full text |Cite
|
Sign up to set email alerts
|

Pathological features and their prognostic impacts on oral cavity cancer patients among different subsites – A singe institute’s experience in Taiwan

Abstract: We investigated the relationship of different primary subsites together with their pathological features on the survival of oral cavity squamous cell carcinoma (OCSCC) patients. We retrospectively reviewed OCSCC patients and documented their demographic data, pathological features and clinical outcome. The Cox proportional hazard model was used to examine the influence of various pathological features on the prognosis in different subsites of oral cavity. There were totally 1,383 OCSCC patients enrolled for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 30 publications
(46 reference statements)
1
52
1
Order By: Relevance
“…Retrospective studies have posited PNI as a predictor or higher rates of occult cervical metastases and regional failure in multivariate analyses incorporating tumor thickness, but not DOI . In addition, PNI has been associated with worse DSS for stage I/II oral tongue SCC on multivariate analysis in a model which did not incorporate tumor thickness or DOI . In a recent multivariate analysis, PNI was associated with worse OS, which incorporated AJCC 8th edition T staging into the model (which therefore did necessarily stratify by DOI).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have posited PNI as a predictor or higher rates of occult cervical metastases and regional failure in multivariate analyses incorporating tumor thickness, but not DOI . In addition, PNI has been associated with worse DSS for stage I/II oral tongue SCC on multivariate analysis in a model which did not incorporate tumor thickness or DOI . In a recent multivariate analysis, PNI was associated with worse OS, which incorporated AJCC 8th edition T staging into the model (which therefore did necessarily stratify by DOI).…”
Section: Discussionmentioning
confidence: 99%
“…Scientists revealed that the expression of NUDT1 improves the invasion and metastasis of various tumors by activating different enzymes and signaling pathways . The degree of tumor invasion and metastasis largely determines the prognosis of patients with OSCC . In this research, we analyzed the OS and TSS of patients with OSCC and found that the OS and TSS of OSCC patients in high NUDT1 expression group were lower than those in the low NUDT1 expression group, which means the high NUDT1 expression had a poorer prognosis than those with low NUDT1 expression.…”
Section: Discussionmentioning
confidence: 87%
“…[22][23][24] The degree of tumor invasion and metastasis largely determines the prognosis of patients with OSCC. 25 In this research, we analyzed the OS and TSS of patients with OSCC and found that the OS and TSS of OSCC patients in high NUDT1 expression group were lower than those in the low NUDT1 expression group, which means the high NUDT1 expression had a poorer prognosis than those with low NUDT1 expression. Further analysis proved that NUDT1 was an independent prognostic factor for OS and TSS of patients with OSCC.…”
Section: Discussionmentioning
confidence: 91%
“…5,6 With the introduction of DOI in the new AJCC staging, there is a concern whether adjuvant radiation should be added based on DOI alone. There is a limited literature on evaluation of LVSI as an isolated prognostic factor and authors are divided in their opinion with some suggesting it to be a poor prognosticator [16][17][18] while others suggest the contrary. Various histopathological factors depth of invasion (DOI), PNI, LVSI, grade of the tumor) have been studied previously that could affect survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, in the present study PNI was not found to be significant prognosticator on multivariate analysis both for recurrences and DSS. There is a limited literature on evaluation of LVSI as an isolated prognostic factor and authors are divided in their opinion with some suggesting it to be a poor prognosticator [16][17][18] while others suggest the contrary. 19 In the present study, it was found that LVSI was a significant prognosticator of DSS both on univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%